Effect of poling time on piezoelectric properties of 0-3 PZT-Portland cement composites - A. Chaipanich (2018)
Lead zirconate titanate (PZT)-Portland cement (PC) composites were produced and the effect of poling time on the piezoelectric properties such as piezoelectric coefficient (d33) and electromechanical coupling coefficient (Kt) of 0-3 connectivity PZT-Portland cement (PC) composites were investigated. PZT-PC composites were produced using PZT of 60% by volume and the poling time of 15, 30, 45, 60 and 90 minutes were used. The results showed that when using the poling time at 45 minutes, the d33and Ktvalues were found to be highest at 28 pC/N and 19.87%, respectively.